Impact of Fermented Wheat Bran Dietary Fiber Addition on Dough Rheological Properties and Noodle Quality - Fan, Ling; Li, Li; Xu, Anmin; Huang, Jihong; Ma, Sen (Frontiers in Nutrition, 2022)
This study aimed to evaluate the effect of fermented wheat bran dietary fiber (FWBDF) on the rheological properties of the dough and the quality of noodles and to compare it with the effect of the unfermented WBDF (UWBDF). WBDF was fermented with Auricularia polytricha. The results showed that adding UWBDF/FWBDF increased the storage modulus G' and loss modulus G” of the dough, converted α-helices and β-turns into β-sheets and random coils, respectively, inhibited water flow, increased cooking loss, and decreased the maximum resistance in the noodles. The formed gluten network had a more random and rigid structure, resulting in the deterioration of the quality of noodles. Furthermore, the number of α-helices and the peak proportions of weakly bound water A22 increased but the number of β-sheets and cooking loss decreased in the FWBDF group compared with the UWBDF group. FWBDF (≤4%) improved the hardness of noodles, while UWBDF decreased it. These changes indicated that fermentation could reduce the destructive effects of WBDF on the quality of noodles, providing a new perspective on balancing dietary fiber-rich and high-quality foods.